Maxillofacial Manifestations of Crohn's Disease: clinical and dental considerations (Research, Society and Development, 2022)
Crohn's disease (CD) is a chronic inflammatory bowel disease (IBD) of the gastrointestinal tract of unknown cause. However, it is known that environmental factors, epigenetics, intestinal microbiota and genetic factors are known to play a significant role in the etiology of the disease. Thus, this study aimed to review the literature on oral manifestations resulting from Crohn's Disease, as well as the proper management of oral lesions. As methodological procedures, a literature review is adopted using the SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, with the help of the Mendeley reference manager. The results indicate that oral lesions resulting from Crohn's Disease include lip edema, granulomatous nodular edema, deep linear ulcerations, mucogingivitis, aphthous ulceration, angular cheilitis and pyosestomatitis vegetans. The dentist must give the patient the necessary help by providing information on hygiene techniques and suggesting an increase in the number of consultations to control the manifestations. You must consult with the gastroenterologist to adjust the control of pharmacological therapy, all with the aim of providing the best alternative for the patient and improving their quality of life.